Diversity of IQ, EQ and SQ in Islamic Education - Saepulah, Saepulah; Alfi, Muhammad; Satria, Nugraha; Mubarok, Isrok; Mulyanah, Nuneng; Hodijah, Siti (EDUTEC : Journal of Education And Technology, 2025)
The diversity of IQ (Intellectual Quotient), EQ (Emotional Quotient), and SQ (Spiritual Quotient) should be recognized and embraced within Islamic education. Islamic teachings, as conveyed through the Qur’an and the Sunnah, have long acknowledged and provided guidance on the variety of human intelligences. This article employs a qualitative literature review to explore the integration of these three intelligences. The analysis concludes that an integrative understanding of IQ, EQ, and SQ is crucial for developing well-rounded individuals, as it helps students appreciate the divine will of Allah SWT, encourages respect for individual differences, and ensures all forms of intelligence are guided by Islamic principles. The study finds that each intelligence plays a distinct and vital role: IQ facilitates logical reasoning and critical thinking, EQ supports emotional regulation and empathy, and SQ fosters a deeper connection with Allah, enhancing sincerity in worship (khusyu’). Ultimately, the article demonstrates how Islamic education, through this integrative approach, aspires to nurture the ideal human being (insan kamil) who is intellectually capable, emotionally balanced, and spiritually grounded, thereby contributing positively to both individual development and society at large.